CARBON NANOTUBES: A NOVAL CARRIER SYSTEM FOR DRUG DELIVERY & CANCER THERAPY - ABHINAV SHAHI, (International Journal of Pharma and Bio Sciences, 2014)
Carbon nanotubes (CNTs) have been introduced recently as a novel carrier system for both small and large therapeutic molecules. CNTs can be functionalized (i.e., surface engineered) with certain functional groups in order to manipulate their physical or biological properties. Carbon nanotubes (CNTs) are allotropes of carbon with a cylindrical nanostructure. CNTs made from a single graphene sheet results in a single-walled nanotubes (SWNT) while several graphene sheets make up multiwalled carbon nanotubes (MWNTs). This paper will discuss the therapeutic applications of CNTs with a major focus on their applications for the treatment of cancer.